Development of a quantitative self-assessment tool for hospital antimicrobial stewardship and infection control programs: a step towards standardizing clinical studies - Zanichelli, V.; Zakariah, S. Z.; Classen, A. Y.; Dumpis, U.; Giske, C. G.; Goepel, S.; Hagen, D.; Jorgensen, S. B.; Kessel, J.; Kjellander, C.; Kleppe, L. K.S.; Simonsen, G. S.; et al. (Oxford University Press, 2026)
Background Antimicrobial stewardship (AMS) and infection prevention and control (IPC) programs are crucial for reducing antimicrobial resistance in hospitals. Existing quality indicators (QIs) for these programs are mainly qualitative, hindering external benchmarking. PILGRIM (NCT03765528) is a prospective multinational cohort study evaluating the impact of antibiotic prescription quality on intestinal domination by healthcare-associated pathogens. Objective In this sub-study, we develop a quantitative scoring tool for AMS and IPC programs to facilitate standardized assessments of programs and support clinical studies. Methods We used a RAND-modified Delphi consensus procedure to establish a scoring system for AMS and IPC programs. The tool was tested using data collected from eight hospitals in five countries during 2019-2024. We evaluated temporal associations between scores, Clostridioides difficile cases, hand disinfectant and antibiotic use. Results We assessed 98 QIs, resulting in in a final set of 62 QIs (35 for AMS and 27 for IPC). For our sites, the overall median score was 29 out of 50 (IQR 28-31) for AMS and 36 out of 50 (IQR 33-38) for IPC programs. Higher-scoring sites decrease antibiotic use over time. IPC scores were positively correlated with hand disinfectant use. Conclusion This quantitative scoring scheme represents a promising step towards standardizing assessments of AMS and IPC programs in high-income settings, enabling external comparisons and supporting future clinical studies. Further validation is needed to refine its predictive validity and ensure its utility in diverse healthcare settings.